Macroeconomic policy under high uncertainty lessons from pandemics and crises ("Journal "U". Economy. Management. Finance.", 2026)
This article examines the features of macroeconomic policy in conditions of high uncertainty. Using the examples of pandemics and geopolitical crises, the adopted measures are analysed and key lessons for economic policy are formulated.
Keywords: мacroeconomic policy; uncertainty; pandemic; geopolitical crisis